Chemoreactome screening of aquacobalamin and heptamethyl ester of cyanoaquacobyrinic acid cytotoxic effects on tumor cells with experimental confirmation on BT-474 and A549 cell - I. Yu. Torshin; M. V. Filimonova; O. A. Gromova; L. A. Maiorova; M. A. Sorokina; D. E. Frolova; A. N. Gromov; I. A. Reyer (IRBIS LLC, 2024)
Background. The search for an effective and safe pharmacotherapy for tumor diseases includes the evaluation of the action of candidate molecules on various types of tumor cells. Vitamin B12 and its derivatives are promising molecules whose properties can be controlled through chemical modifications.Objective: conducting in silico chemoreactom screening and in vitro experimental study of aquacobalamin and heptamethyl ester of cyanoaquacobyrinic acid (HECСA).Material and methods. Chemoreactome screening was carried out on the basis of a problem-oriented theory of chemograph isomorphism analysis, which is an extension of the algebraic approach to machine learning and recognition problems. Trainable algorithms for calculating chemical distances between molecules were used, on the basis of which the values of half-maximal inhibitory concentration (IC50) were calculated. Screening was carried out for 470 cultures of human tumor cells, including SNB19 (astrocytoma), HCT116 (colon cancer), HeLa (cervical carcinoma), BT-474 (breast duct carcinoma), and A549 (lung carcinoma) cell lines. Dicyanocobyric acid heptamethyl ester ((CN)2Cby(OCH3)7) was obtained by boiling a solution of vitamin B12 in methanol with sulfuric acid (1.0 M) for 4 days. HECСA ((CN)(H2O)Cby(OCH3)7) was obtained by vacuum drying an aqueous solution of (CN)2Cby(OCH3)7 (pH 4.0 and 25 °С). The ester structure and purity were confirmed by 1H nuclear magnetic resonance data, elemental analysis, and MALDI-ToF (matrix-assisted laser desorption/ionization time of flight) mass spectroscopy. Experimental studies of tumor cell cultures were carried out using the MTT testwith aquacobalamin and HECСA on cell lines of immortalized (telomerized) fibroblasts (Fb-hTERT), lung carcinoma (A549), and breast duct cancer (BT-474).Results. Chemoreactome screening of the effects of molecules on tumor cells made it possible to obtain estimates of cell growth IC50 for 470 tumor cell lines. Depending on cell line and vitamin B12 derivative molecule, IC50 values varied in a fairly wide range: from 15 to 2000 nM. In vitro studies on cultures of two human tumor cell lines (BT-474 and A549) and telomerized Fb-hTERT fibroblasts confirmed the cytotoxic effect of aquacobalamin and its hydrophobic derivative HECСA. It was shown that aquacobalamin had weak cytotoxic properties in the concentration range of 3.125-200 µg/l (IC50 > 200 nM), and HECСA significantly reduces the survival of BT-474 and A549 tumor cell lines at high concentrations (100-200 µg/l, IC50 about 100 nM).Conclusion. Correspondence was shown between the results of in silico chemoreactome screening and in vitro cell culture studies: IC50 values for HECСA were significantly lower than for aquacobalamin, and the conversion factor from chemoreactome estimates to experimental ones was almost the same (2.64 for BT-474, and 2.63 for A549). The results of chemoreactome screening for other tumor cell lines can be used to plan further cell experiments with vitamin B12 derivatives.